Algoritma Haversine pada Sistem Informasi Geografis: Tinjauan Literatur Sistematis: Tinjauan Literatur Sistematis - Hasanah, Mau'idzoh; Suharso, Aries (NUANSA INFORMATIKA, 2023)
Along with the times, more and more developments are being carried out, starting from the construction of buildings, housing, supermalls, hotels, and so on. More and more buildings cause the order on the earth's surface to change and make more and more roads. Roads are becoming more and more narrow, making it difficult for people to travel to a destination, especially in foreign areas. Departing from this problem, there is anxiety among the people who do not know the distance to their destination, making it difficult to go anywhere. However, with the presence of increasingly developing technology, it can be used as a practical solution to this problem. The technology that can be utilized is called a Geographic Information System (GIS). With the help of the haversine algorithm for distance calculation, GIS provides geographic information on the earth's surface in the form of a system. This review aims to present a comprehensive picture of the accuracy of the haversine algorithm in geographic information systems that is useful for helping these community problems